Post-traumatic Stress Symptoms and Serotonin Transporter (5-HTTLPR) Polymorphism in Breast Cancer Patients - Zerbinati, Luigi; Murri, Martino Belvederi; Caruso, Rosangela; Nanni, Maria Giulia; Lam, Wendy; De Padova, Silvia; Sabato, Silvana; Bertelli, Tatiana; Schillani, Giulia; Giraldi, Tullio; Fielding, Richard; Grassi, Luigi (Frontiers in Psychiatry, 2021)
Introduction: Post-Traumatic Symptoms (PTSS) and Post-traumatic Stress Disorder (PTSD) are conditions relatively common in Psycho-Oncology. Several studies have examined the relationship between serotonin transporter gene-linked polymorphic region (5-HTTLPR) and cancer, however no studies have yet explored Gene-Environment interactions between this polymorphism and specific forms of distress, such cancer related problems (CRP) or life stressful events (LSE). Methods: 145 female participants affected by breast cancer were recruited from Medical Oncology out-patient and day-hospital clinics. Patients were assessed using the Impact of Event Scale (IES), the Problem List (PL) of the NCCN tool and the Paykel’s Life Events Interview to evaluate the exposure to LSE during the year before the cancer diagnosis; they were subsequently genotyped for 5-HTTLPR polymorphism by analyzing genomic DNA obtained from whole blood cells. Gene-Environment interactions were tested through moderation analysis. Results: 26 patients (17.7%) were classified as PTSS cases using the IES. Genotype and phenotype distributions did not differ across individuals with/without PTSS (genotype: χ2=1.5; df=2; p=0.3; phenotype χ2=0.9; df=1; p=0.2). For both the triallelic and the biallelic model, using CRP as a predictor showed significant gene-environment interactions with IES total score (p=0.020 and p=0.004 respectively), with individuals carrying the l/l allele showing a greater risk of developing PTSS. On the other hand, no interaction was found in relationship to LSE (p=0.750) Conclusion: this study showed a significant gene-environment interaction between CRP and PTSS in breast cancer patients, with carriers of the l/l allele showing greater sensitivity to stress.